Influence Of Product Quality Price And Promotion On Customer Purchase Decision at PT. Socfin Indonesia (Socfindo) - Nurmaidah Ginting; Mikha Situmorang; Ruth Yohana; Elisa Pebrina; Ridwan Syahputra (CERED Indonesia Institute, 2022)
Researcher chooses object research at PT. SOCFIN INDONESIA (SOCFINDO), because experience problem sale in 3 years final consequence covid 19 pandemic. About theory used for support study is a theory according to experts part management related marketing with quality products, prices and promotions. The researcher use population customers as many as 91 people with sample research used for results from the validity and reliability test of as many as 30 customers at PT. Socfin Indonesia (SOCFINDO). Research results show Quality products, prices and promotions by Partial take effect significant on decision customer. simultaneous Quality Products, Prices and Promotions take effect significant on decision purchase. With score coefficient, the determination seen of Adjust R Square is 0.593 which means influence variable free (Quality products, prices and promotions) top variable bound (Purchase Decision) by 59.3% and more of 40.7% is influence from variable independent foreigners who don't researched in research this like brand, quality service etc. PT. Socfin Indonesia (SOCFINDO) is companies engaged in plantation coconut palm oil and rubber, as well as sale seeds and seeds coconut palm quality high. PT. Socfin Indonesia (SOCFINDO) was established in 1930 as a company Socfindo Medan.